UJI EFEKTIVITAS ANTIHIPERGLIKEMIA KOMBINASI JUS MENTIMUN (Cucumis sativus) DAN TOMAT (Solanum lycopersicum L) TERHADAP TIKUS WISTAR JANTAN - Suntoro; Susanti, Ressi; Robiyanto (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2017)
Diabetes mellitus is a metabolic disease with characteristics of hyperglycemia. Conventional treatments using oral medications such as glibenclamide and metformin have many side effects. Therefore, it is necessary to find an alternative drug that is more effective and safer. Some agents that are often used as anantihiperglikemia are cucumber and tomato.The purpose of this study was to determine the effectiveness of combination of cucumber and tomato juice to decrease blood glucose levels of male Wistar ratsusingglucose tolerance method. Male Wistar rats were fasted for 10 hours and then measured the levels of fasting blood glucose. Then animals test were given the juice (single and combination), 30 minutes later were given a dose of sucrose load of 6.75 g / KgBW orally. Blood glucose levels of animal testre-measured at 30th, 60th, 90th, and 120th minutes after loading sucrose using a glucometer.The measurement results showed that blood glucose levels of the combination of cucumber and tomato juice group with dose ratio of 28 g/KgBW:16.8 g/KgBW gave decrease blood glucose levels significantly compared to the negative control group (p≤0.05) and didn’t not provide a significant difference compared to the metformin group (p ≥0.05).